COVID-19 vaccination roll-outs in eleven small countries within the WHO European region; Lessons learned - Palmer, Katie; Nemer, Leda; Datta, Siddhartha Sankar; Menne, Bettina Maria (Frontiers in Public Health, 2022)
The development and administration of COVID-19 vaccines has been an essential element in controlling the COVID-19 pandemic. However, countries worldwide have faced challenges in planning and implementing vaccination strategies. The aim of the current perspectives paper is to describe the situation faced by small countries in the WHO European Region in implementing their national vaccination strategies during the first stages of the planned roll-out (up to May 2021). This paper uses information from the WHO Small Countries Initiative (SCI), which includes a network of 11 countries with populations of <2 million (Andorra, Cyprus, Estonia, Iceland, Latvia, Luxembourg, Malta, Monaco, Montenegro, San Marino, and Slovenia). The SCI countries faced many challenges including: a lack of appropriate vaccination centers, adequate workforce, and registration/booking systems to coping with the unprecedented vaccine storage and administration demands; difficulties for high-risk groups (e.g., older individuals and those with health problems or cognitive impairment) to access vaccination sites or use digital registration/booking systems; vaccine wastage due to cancelled appointments; inequalities in vaccine uptake. Innovative programmatic interventions were implemented to facilitate the vaccination uptake of the populations such as; the creation of non-medical vaccination sites and mobile vaccination units; on-site vaccination of people in long-term residential facilities and long-term medical wards; diversifying health workforce like redeployment of healthcare professionals and use of medical students and retired medical professionals; campaigns with clear information to the general public (in multiple languages where necessary) both offline and online; use of digital registration/booking systems and alternative (non-digital) registration/booking systems for relevant individuals and; administration of excess vaccine doses to non-priority groups to avoid wastage.